Concurrence of the strengths and difficulties questionnaire and developmental behaviour checklist among children with an intellectual disability. Issue 2 (5th October 2017) - Rice, L. J.; Emerson, E.; Gray, K. M.; Howlin, P.; Tonge, B. J.; Warner, G. L.; Einfeld, S. L.
Abstract: Background: The Strengths and Difficulties Questionnaire (SDQ) is widely used to measure emotional and behavioural problems in typically developing young people, although there is some evidence that it may also be suitable for children with intellectual disability (ID). The Developmental Behaviour Checklist – Parent version (DBC‐P) is a measure of emotional and behavioural problems that was specifically designed for children and adolescents with an ID. The DBC‐P cut‐off has high agreement with clinical diagnosis. The aim of this study was to estimate the relationship between DBC‐P and SDQ scores in a sample of children with ID. Method: Parents of 83 young people with ID aged 4–17 years completed the parent versions of the SDQ and the DBC‐P. We evaluated the concurrent validity of the SDQ and DBC‐P total scores, and the agreement between the DBC‐P cut‐off and the SDQ cut‐offs for 'borderline' and 'abnormal' behaviour. Results: The SDQ total difficulties score correlated well with the DBC‐P total behaviour problem score. Agreement between the SDQ borderline cut‐off and the DBC‐P cut‐off for abnormality was high (83%), but was lower for the SDQ abnormal cut‐off (75%). Positive agreement between the DBC‐P and the SDQ borderline cut‐off was also high, with the SDQ borderline cut‐off identifying 86% of those who met the DBC‐P criterion. Negative agreement was weaker, with the SDQ borderline cut‐off identifying only 79% of the participants who did not meet the DBC‐P cut‐off. Conclusion: The SDQ borderline cut‐off has some validity as a measure of overall levels of behavioural and emotional problems in young people with ID, and may be useful in epidemiological studies that include participants with and without ID. However, where it is important to focus on behavioural profiles in children with ID, a specialised ID instrument with established psychometric properties, such as the DBC‐P, may provide more reliable and valid information.